Evaluation of morinda citrifolia ethanolic extract versus morinda citrifolia fresh fruit juice for tissue response and systemic toxicity in animal model - Kavalipurapu Venkata Teja; Sindhu Ramesh; Karthik Ganesh; Kaligotla Apoorva Vasundhara (Wolters Kluwer Medknow Publications, 2021)
Introduction: An ideal irrigant should exhibit good antimicrobial activity along with smear removal. Various plant extracts have been used for disinfection of the root canal system. The present study aims in evaluating the tissue response and systemic toxicity of ethanolic extract of Morinda citrifolia versus Morinda citrifolia fresh fruit juice in an animal model. Materials and Methods: A total 48 female adult wistar albino rats were randomly allocated into 4 groups as Group I- 3% sodium hypochlorite (n = 12), Group II- Saline (Control) (n = 12), Group III- ethanolic extract of Morinda citrifolia (n = 12), Group IV- Morinda citrifolia Fresh Fruit Juice (n = 12). A trough was made in the periapical bone, and the test sample was placed in the respective groups. The animals were euthanized for 7th day, 14th day and 30th day and the tissue specimen was prepared for histopathological evaluation, and serum analysis was done for oxidative stress markers, liver and renal function tests. Results: Serum analysis exhibited significant elevation of Alkaline Phosphatase (ALP), Glutathione Peroxidase (GPX) and Glutathione Reductase (GR) and histopathology showed a higher inflammatory response at 7th and 14th days in group II and group III (p < 0.05), as compared to the other groups. At the 30th day time interval, there was no statistically significant difference in serum analysis and inflammatory response, in all the four groups analysed (p > 0.05). Conclusion: Ethanolic extract of Morinda citrifolia was not biocompatible and more cytotoxic than a Morinda citrifolia fresh fruit juice. So, fresh fruit juice of Morinda citrifolia can be a preferred choice of natural root canal irrigant, with least possible cytotoxic effects as compared to the ethanolic extract.